Lessons Learnt from Gauging Software Metrics of Cabin Software in a Commercial Airliner. (15th October 2012) - Burger, Stefan; Hummel, Oliver
Abstract : In order to achieve high safety standards, avionic software needs to be developed with very high requirements regarding safety, reliability, and determinism as well as real-time constraints, which are often in conflict with the development of maintainable software systems. Nevertheless, the ability to change the software of an airplane is of increasing importance, since it consists of a multitude of partially hardware-specific subsystems which may need replacement during a plane's lifespan of typically numerous decades. Thus, as a first step towards optimizing maintainability of avionic software we have benchmarked the cabin software of a commercial airliner with common software metrics. Such a benchmarking of avionic software contributes valuable insights into the current practice of developing critical software and the application of software metrics in this context. We conclude from the obtained results that it is important to pay more attention to long-term maintainability of aviation software. Additionally we have derived some initial recommendations for the development of future avionic software systems.